Theory Follows Photography: The Evolving Gaze of Denise Scott Brown - Meninato, Pablo (UI Scholars Hub, 2023)
Throughout history, architects have communicated their ideas through writing, drawing, model-making, speculation, and built work. Photography, which appeared in architecture books at the beginning of the 20th century, was mostly considered to be ancillary to the written word. A recent exhibition of photographs by Denise Scott Brown at Tyler School of Art and Architecture in Philadelphia during summer 2021 demonstrates the possibility of another creative and intellectual path for the medium. Photography simultaneously serves as a precedent and catalyst for architectural and urban thinking and theory. This article aims to examine the relationship and continuity between Scott Brown's photographs and the ideas that she conveyed in essays and books. Photography, therefore, becomes the catalyst for writings that integrate disparate topics, such as anthropology, vernaculars, history, and Pop Art, as the iconology of Las Vegas and the changing urban landscape of Philadelphia. Embodying a new creative paradigm, Scott Brown's photography anticipates theory.